Analysis of Educational Values in Literary Discourse - Maksura, Ainul .; Hasmawati, Hasmawati; Muthmainnah, Sitti (Universitas Negeri Makassar, 2025)
Abstract. This study is a linguistic-literary research that aims to describe the educational values in the discourse in short story of Syajaratul Haya' by Ruhi Demiral. The data analysis techniques used are data reduction, data presentation, and verification and conclusion. The data in this study are in the form of quotations or sentences contained in short stories, while the data source is the short story Syajaratul Haya by Ruhi Demiral. The data collection techniques in this research are reading technique and note-taking technique. The results of this study show that the short story of Syajaratul Haya has four educational values were found in this short story, namely religious, moral, social and cultural educational valuesKeyword: Syajaratul Haya Short Story, Educational Values, lierature